Robust Cobalt Manganese Sulfide Thin Film as an Electrocatalytic Layer for Quantum Dot-Sensitized Solar Cells with the Polysulfide Electrolyte - Cheng, Yao-Sheng; Wu, Yu-Ting; Aulia, Sofiannisa; Chang, Ching-Cheng; Rinawati, Mia; Lee, Ting-Ying; Chang, Jia-Yaw; Septiani, Ni Luh Wulan; Yuliarto, Brian; Yeh, Min-Hsin (ACS sustainable chemistry & engineering, 2023)
A quantum dot-sensitized solar cell (QDSSC) is a promising next-generation photovoltaic technology due to its clean, low cost, high efficiency, and easy fabrication. To date, various transition-metal sulfides (TMSs) have been demonstrated, yet the utilization of bimetallic sulfides has rarely been reported. While the bimetallic TMS has excellent chemical and physical properties, it displayed improved activity and stability as a counter electrode (CE) in QDSSCs with polysulfide electrolytes. In this regard, a simple yet affordable method is developed for manufacturing CEs based on cobalt manganese sulfide (CMS) composites. Herein, cobalt manganese oxyhydroxide was first deposited on the fluorine tin oxide substrate by a single-step redox process and then sulfurized to CMS. By controlling the precursor ratio of Co and Mn, the bimetallic CMS could be adjusted to manipulate the S n 2– reduction activity. Taking the advantage of those bimetallic systems, their synergistic effects demonstrated superior long-term stability in a different multi-cyclic voltammetry treatment than conventional CuS CEs. Notably, the QDSSCs with optimized CMS CEs also exhibited a high solar-to-electricity conversion efficiency (η) of 5.88 ± 0.19% under 100 mW cm–2 irradiation, indicating that CMS CE exhibited superior reduction activity to S n 2–.